Pelatihan Teknik Dasar Pembuatan Mahar di UPTD SPNF Ungaran - Arina Haq (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
One of the business opportunities that will always exist in the future is wedding dowry making services. SKB Ungaran has created a training program which will later be used as preparation for opening a business in the field of dowry making services and improving the skills of participants who successfully pass the selection, the majority of whom are housewives and women who are still of productive age. Dowry is a form of expression of love and commitment in marriage, a tradition that is still maintained today. The methods used in delivering the material are interactive methods, demonstrations and questions and answers. The 3 methods are divided into several planning, implementation and evaluation activities. Planning activities begin with preparing materials and tools and materials used. Implementation activities begin with direct practice by participants after observing demonstrations from resource persons, making various techniques for folding banknotes in various shapes such as flower petals, animal shapes, rolling techniques and reassembling them into prepared media by adding garnitures in the form of artificial flowers, writing and other garnitures such as beads. This training produces a product in the form of a series of dowries that have been assembled into one wooden figure. During the activity, the participants were enthusiastic and serious in making a series of dowries according to the concept that had been planned and the finished products had various results and the creativity of the participants was seen with different results but they were still creative between each participant.